Pengaruh Label Halal, Sosial Media Advertising, Perceived Brand Interactivity Terhadap Keputusan Pembelian Kosmetik Wardah Di Kota Salatiga Melalui Kepercayaan Sebagai Variabel Interveing - Yevy Januarti Rosuda; Ahmad Samingan (Al-Muraqabah: Journal of Management and Sharia Business, 2023)
This study aims to determine how strong the influence of Halal Labels, Social Media Advertising, Perceived Brand Interactivity on the purchase decision of Wardah cosmetics in Salatiga through trust as an intervening variable using quantitative methods. In this study, primary data was sorted with the population of Wardah cosmetics users. Sampling technique with purposive sampling method using certain criteria for 100 respondents. The analysis used is descriptive statistical tests, instrument tests, classical assumption tests, statistical tests, hypothesis tests and path analysis. Based on this study obtained the results: Halal label has no positive and significant influence on trust. Social media advertising has a positive and significant effect on trust. Perceived brand interactivity has a positive and significant effect on trust. Trust negatively affects purchasing decisions. The halal label has a positive and significant influence on the purchasing decision. Social media advertising negatively affects purchasing decisions. Perceived brand interactivity negatively affects purchasing decisions. Halal label has a positive effect on purchasing decisions through trust. Social media advertising positively and significantly affect consumer satisfaction through trust. Perceived brand interactivity has a positive and significant effect on purchasing decisions through trust.